1991
DOI: 10.1007/bf01912797
|View full text |Cite
|
Sign up to set email alerts
|

Heat of adsorption of carbon dioxyde and ethene on zeolites a exchanged with Li+, Ni2+ and Cu2+

Abstract: Various contents of Li +, Ni 2+ or Cu z+ were introduced in zeolite NaA by conventional cation exchange. Crystal damages are observed on samples having suffered the lower pH.The heat of adsorption of CO2 and CzI-I4 was determined by isothermal calorimetry. Very high initial heats (100-120 kJ tool -1) are found in NaA as well as in Li + exchanged samples, perhaps due to chemisorption on alkaline cations; they vanish when Ni 2+ or Cu 2+ replaces more than 20% of Na +, in like manner with Co 2+ or Zn 2+. For the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Results consistent with these observations have been reported by others for CO 2 adsorption on X zeolite [38], Cu(x)A [34], Zn(x)A [39], Na-ZSM-5 [22], and Na-G [14]. The weak character of adsorbate-adsorbate interactions could be due, as mentioned before, to the physisorbed state of CO 2 .…”
Section: Isosteric Heat Of Adsorptionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results consistent with these observations have been reported by others for CO 2 adsorption on X zeolite [38], Cu(x)A [34], Zn(x)A [39], Na-ZSM-5 [22], and Na-G [14]. The weak character of adsorbate-adsorbate interactions could be due, as mentioned before, to the physisorbed state of CO 2 .…”
Section: Isosteric Heat Of Adsorptionsupporting
confidence: 91%
“…This evolution was also reported in the case of CO 2 adsorption on Cu(x)X [20] and Cu(x)A [34]. The continuous decrease in isosteric heat with the introduction of Cr 3+ could be ascribed to a progressive weakening of electrostatic fields present within zeolitic cavities.…”
Section: Isosteric Heat Of Adsorptionmentioning
confidence: 51%
“…Numerous papers concerning CO 2 adsorption on zeolites A (Delaval and De Lara 1981;Amari et al 1991), faujasites X and Y (Barrer and Gibbons 1965;Khelifa et al 1999;Hasegawa et al 2001;Walton et al 2006;Plant et al 2006), mordenites (Amari et al 1992), ZSM-5 (Yamazaki et al 1993;Dunne et al 1996;Katoh et al 2000), and chabazites (Zhang et al 2008) can be found in the literature investigating CO 2 adsorption to determine the effect of the structure and cation type on the adsorption equilibrium and energetics of the adsorption process. Much research effort has been focused on the CO 2 adsorption on NaX and NaY at ambient temperature (Maurin et al 2005;Plant et al 2006Plant et al , 2007 and more recently in NaY and LiY at high temperatures ) using a combination of Grand Canonical Monte Carlo simulations and microcalorimetry/gravimetry measurements.…”
mentioning
confidence: 98%
“…On the contrary, the initial region gets narrower and narrower when sodium is exchanged for transition metal cations (Ni ~ § Cu2+: Fig. 1 and [33]; Co 2+ and Zn 2+ [32]. It vanishes when the exchange level reaches ca.…”
Section: Methodsmentioning
confidence: 91%